2015
DOI: 10.1587/transinf.2014edp7168
|View full text |Cite
|
Sign up to set email alerts
|

Phoneme Set Design for Speech Recognition of English by Japanese

Abstract: SUMMARYThis paper describes a novel method to improve the performance of second language speech recognition when the mother tongue of users is known. Considering that second language speech usually includes less fluent pronunciation and more frequent pronunciation mistakes, the authors propose using a reduced phoneme set generated by a phonetic decision tree (PDT)-based top-down sequential splitting method instead of the canonical one of the second language. The authors verify the efficacy of the proposed meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…5 showed that the most highly improved performances appeared at the lowest and highest proficiency levels. The experimental results of our previous studies showed that a single 28-reduced phoneme set provided better performance in comparison with other reduced ones for speech by L2 speakers on average [8]. 25-phoneme and 32-phoneme sets, which have slightly different characters from the 28-phoneme set, were assigned as the proficiency-dependent reduced phoneme set to L2 speakers of lowest and highest proficiency levels, respectively.…”
Section: Figmentioning
confidence: 97%
See 4 more Smart Citations
“…5 showed that the most highly improved performances appeared at the lowest and highest proficiency levels. The experimental results of our previous studies showed that a single 28-reduced phoneme set provided better performance in comparison with other reduced ones for speech by L2 speakers on average [8]. 25-phoneme and 32-phoneme sets, which have slightly different characters from the 28-phoneme set, were assigned as the proficiency-dependent reduced phoneme set to L2 speakers of lowest and highest proficiency levels, respectively.…”
Section: Figmentioning
confidence: 97%
“…To carry out the preliminary splitting, we utilized 166 discrimination rules [8] that were designed to categorize each phoneme on the basis of phonetic features such as the manner and position of articulation. A selection of these discrimination rules is shown in Table A· 1 (appendix).…”
Section: Criterion Of Determining Phoneme Setmentioning
confidence: 99%
See 3 more Smart Citations